Analisis Kandungan Merkuri dalam Sedimen dan Keong Sawah (Pila Ampullacea Linn.) Danau Lebo Sumbawa Barat - Nabila, Riska; Purwati, Nining; Jayanti, Ervina Titi (Teknik Lingkungan Universitas Islam Indonesia, 2024)
Traditional gold mining around Lake Lebo has a positive impact on people's income, but it has a negative impact on the waters of Lake Lebo. This is evidenced by a 2016 study conducted on 2016 that reported mercury pollution in the sediments and fish of Lake Lebo. The objective of this study is to determine the mercury content in the sediments of Lake Lebo, West Sumbawa. The sampling employed purposive sampling with four research stations based on their utilization around Lake Lebo. The mercury content in the samples was tested using an AAS (Atomic Absorption Spectrophotometer). The sediments of Lake Lebo Meraran contain 0.70 ppm of mercury (lightly polluted). The Meraran Paddy Field Sediment contains 0.31 ppm of mercury (tolerable). The sediments of Lake Lebo Seloto contain 0.22 ppm of mercury (normal). The mercury content in Lake Lebo Rice Snails is less than 0.0001 (undetectable), making them safe for public consumption. Several factors contribute to the undetected mercury in the samples, namely rainfall, floods, waste storage, and phytoremediation by aquatic plants.